Marine Geochemistry - Schulz, Horst D.; Zabel, Matthias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Since 1980 a considerable amount of scientific research dealing with geochemical processes in marine sediments has been carried out. This textbook summarizes the state of the art in this field of research. The topics comprise the examination of sedimentological and physical properties of the sedimentary solid phase, of pore water and pore water constituents, organic matter as the driving force of most microbiological processes, biotic and abiotic redox reactions, carbonates and stable isotopes as proxies for paleoclimate reconstruction, metal enrichments in ferromanganese nodules and crusts as well as in hot vents and cold seeps on the seafloor. A new chapter describes properties, occurrence and formation of gas hydrates in marine sediments. The textbook ends with a chapter on model conceptions and computer models to quantify processes of early diagenesis.
The Solid Phase of Marine Sediments -- Physical Properties of Marine Sediments -- Quantification of Early Diagenesis: Dissolved Constituents in Pore Water and Signals in the Solid Phase -- Organic Matter: The Driving Force for Early Diagenesis -- Bacteria and Marine Biogeochemistry -- Benthic Cycling of Oxygen, Nitrogen and Phosphorus -- The Biogeochemistry of Iron -- Sulfur Cycling and Methane Oxidation -- Marine Carbonates: Their Formation and Destruction -- Influence of Geochemical Processes on Stable Isotope Distribution in Marine Sediments -- Manganese: Predominant Role of Nodules and Crusts -- Quantification and Regionalization of Benthic Reflux -- Input from the Deep: Hot Vents and Cold Seeps -- Gas Hydrates in Marine Sediments -- Conceptual Models and Computer Models.
Keywords: Earth sciences; Geochemistry; Geology; Mineralogy; Sedimentology; Oceanography; Earth Sciences; Oceanography; Geochemistry; Geology; Sedimentology; Mineralogy; Electronic books